Effects of Concentrated Growth Factor and Cervical Lymph Node Metastasis on the Prognosis of Mucoepidermoid Carcinoma of the Parotid Gland - Han, Shang-Zhi; Lv, Xin; Chen, Xi-Bo; Xu, Ying-Ying; Liu, Rui; Zhang, Xing-Le (Nepalese Journal of Cancer, 2020)
Introduction: Mucoepidermoid carcinoma (MEC) is a common salivary gland malignancy. As studies reported on large cases of mucoepidermoid carcinoma of the parotid glands are few, this paper aims to research the effects of clinical and pathological factors, such as applying concentrated growth factor (CGF) on repairing and cervical lymph node metastasis, on the prognosis of mucoepidermoid carcinoma of the parotid gland. Methods: The retrospective analysis of prognostic factors was conducted based on 176 cases with mucoepidermoidcarcinoma of the parotid gland, who received treatment at the Affiliated Hospital of Chengde Medical College during the period of March 2000 to March 2012. Results: The Five-year overall survival rate was 75.57%, while the Five-year tumor-free survival rate was 64.77%. Univariate analysis showed that the influential factors for the prognosis of mucoepidermoid carcinoma of the parotid gland included surgical approach, tumor size, clinical stage, pathological grade, lymph node metastasis, and distant metastasis, etc; among which pathological grade, lymph node metastasis, and distant metastasis were indicated by multivariate analysis to be the independent risk factors. Conclusion: The survival rate of mucoepidermoid carcinoma of the parotid gland is relatively high. Lymph node metastasis, pathological grade, and distant metastasis are the independent risk factors that affect the prognosis of patients with mucous epidermis carcinoma of the parotid gland.